A new genus of millipedes (Diplopoda: Polydesmida: Dalodesmidae) from Tasmania, Australia with a mosaic distribution - Mesibov, Robert (Zootaxa, 2004)
Atrophotergum silvaticum n. gen., n. sp. (type species), A. bonhami n. sp., A. montanum n. sp., A. pastorale n. sp., A sodalis n. sp., and A. wurrawurraense n. sp., are described. The six species have a tightly fitted mosaic distribution in Tasmania. Atrophotergum species are among the 'head + 19 segments' Australasian dalodesmids witha  conspicuous pit on the underside of somite 2 in males, and relatively small metatergites on somites 3 and 4 in both sexes. The solenomerite in Atrophotergum is carried on a large posterior projection arising midway along the telopodite.